Preschool Children’s National Art Experience, Accumulated by Developing Their Creativity through Folk Art - Stankevičienė, Kristina (Acta Paedagogica Vilnensia, 2003)
The article reveals how the development of creativity of children from 4 to 6 years through folk art influences on the alternation of experience of folk art, on the enrichment of their world-view using accessible cultural values, over the rise of the sensual elements of national originality, over the maturing process of children for school. The article builds upon the theoretical and empirical researches of creativity development in preschool children through folk art, performed in 1996-2000. A model has been created in order to develop the creativity of children from 4 to 6 years through folk art, the essence of which has been comprised of the augmentation of general educational programmes by folk art, of the synthesis of purposefully selected subject of folk art accessible for children and modern technologies fostering creativity, of children engagement in the activities that broaden their experience of folk art: visual creation, communication and verbal creative expression, creative games, exploring cognition and activities that are close to folk art. The results of the research have shown the efficiency of the model to accumulate children’s experience of folk art and to unfold their creativity. During one year of education their experience of folk art broadened almost twice. Children started showing interest in folk art mare actively, became more observant towards the pieces of artwork, particularly towards the decoration. They could recognize the Lithuanian folk artwork from its patterns, colour, shape, material, technique of accomplishment. Children’s pieces of art have become enriched by the ideas related to mythology, they have started reasoning unusually for children of that age. The experience of that kind has motivated the need of Beauty and Good, children’s creation being contiguous to folk art tradition, benefited the rise of sensational elements of national originality. Playfully and abundantly children have been using the elements of decoration absorbed from folk art and easily modified them and created their own elements. Such drawing has been giving to children a delight in creation and discovery process simultaneously preparing them for development of writing skills at school.